Negative electrode composite material and preparation method thereof, negative electrode, battery and electric equipment

By covering the polymer layer with carboxyl, amide and sulfonic acid groups on the negative electrode material of the lithium-ion battery, the problems of SEI film fragility and lithium ion consumption are solved, and higher battery performance and service life are achieved.

CN119764358APending Publication Date: 2025-04-04HUIZHOU BYD BATTERY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202410433135.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-10
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The solid electrolyte interface (SEI) film is fragile and uneven in lithium-ion batteries, and the volume changes of the negative electrode material cause the SEI film to rupture, lithium ion consumption accelerates, and battery performance is rapidly reduced.

Method used

A negative electrode composite material is used, wherein the negative electrode material is wrapped with a polymer layer having a carboxyl group, an amide group and a sulfonic acid group. The polymer layer is combined with the negative electrode material through hydrogen bonds and ester bonds to form a highly flexible and stable SEI film.

Benefits of technology

It effectively avoids direct contact between the negative electrode material and the electrolyte, slows down the reaction, improves the ion transport rate, extends the life of the SEI film, reduces the consumption of lithium ions, and improves the electrochemical performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764358A_ABST
    Figure CN119764358A_ABST
Patent Text Reader

Abstract

The invention provides a negative electrode composite material and a preparation method thereof, a negative electrode, a battery and electric equipment. The negative electrode composite material comprises a negative electrode material and a polymer layer wrapping the negative electrode material, and the material of the polymer layer comprises carboxyl, acylamino and sulfonic acid group. The polymer layer in the negative electrode composite material is good in flexibility and good in bonding performance with the negative electrode material, so that the negative electrode material can be prevented from being in direct contact with electrolyte, and the reaction between the negative electrode material and the electrolyte is effectively slowed down and reduced; the polymer layer can promote ion transportation and improve the ionic conductivity; the polymer layer can participate in the formation of the SEI film and serve as a main skeleton of the SEI film, and the SEI film formed by the polymer layer is high in flexibility and can effectively avoid cracking, so that the consumption of lithium ions is reduced, and the performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a negative electrode composite material and a preparation method thereof, a negative electrode, a battery and an electrical device. Background Art

[0002] The solid electrolyte interface (SEI) film is formed by the reaction of lithium ions and liquid electrolyte, and serves as the interface layer between the negative electrode and the electrolyte. The SEI film is usually fragile and uneven, and the volume change of the negative electrode material during the charge and discharge process will aggravate the rupture of the SEI film, causing the SEI film to be continuously iteratively generated, consuming more lithium ions, and rapidly reducing battery performance, affecting the use of the battery. Summary of the invention

[0003] In view of this, the present application provides a negative electrode composite material and a preparation method thereof, a negative electrode, a battery and an electrical device.

[0004] In a first aspect, the present application provides a negative electrode composite material, comprising a negative electrode material and a polymer layer wrapping the negative electrode material, wherein the material of the polymer layer has a carboxyl group, an amide group and a sulfonic acid group.

[0005] Optionally, the polymerized monomers of the material of the polymer layer include a first monomer, a second monomer and a third monomer, the first monomer includes the carboxyl group, the second monomer includes the amide group, and the third monomer includes the sulfonic acid group.

[0006] Optionally, the first monomer includes acrylic acid.

[0007] Optionally, the second monomer further includes at least one of an olefin group, a carboxyl group and a hydroxyl group.

[0008] Optionally, the third monomer further includes at least one of an olefin group, a carboxyl group and a hydroxyl group.

[0009] Optionally, the material of the polymer layer includes acrylic acid-alkenylamide-alkenylsulfonate copolymer.

[0010] Optionally, there is a hydrogen bond between the negative electrode material and the polymer layer.

[0011] Furthermore, there is an ester bond between the negative electrode material and the polymer layer.

[0012] Optionally, the thickness of the polymer layer is 1 nm-80 nm.

[0013] Optionally, the coverage rate of the polymer layer on the negative electrode material is greater than 90%.

[0014] Optionally, the particle size D50 of the negative electrode material is 8 μm-16 μm.

[0015] Optionally, the particle size D50 of the negative electrode composite material is 8 μm-16.2 μm.

[0016] Optionally, the specific surface area of ​​the negative electrode composite material is 2m 2 / g-4m 2 / g.

[0017] Optionally, the negative electrode material includes at least one of graphite and silicon-based materials.

[0018] Optionally, the mass ratio of the polymer layer to the negative electrode material in the negative electrode composite material is 0.4%-8%.

[0019] In a second aspect, the present application provides a method for preparing a negative electrode composite material, comprising:

[0020] The prepolymer solution is mixed with the negative electrode material, and after polymerization and drying, a negative electrode composite material is obtained, or the polymer solution is mixed with the negative electrode material, and after drying, the negative electrode composite material is obtained. The negative electrode composite material includes the negative electrode material and a polymer layer wrapping the negative electrode material, and the material of the polymer layer has carboxyl group, amide group and sulfonic acid group.

[0021] Optionally, the prepolymer solution includes a first monomer, a second monomer, a third monomer and an initiator, the first monomer includes the carboxyl group, the second monomer includes the amide group, and the third monomer includes the sulfonic acid group.

[0022] Furthermore, the mass ratio of the first monomer, the second monomer and the third monomer is (1-8):(1-3):(1-4).

[0023] Furthermore, the ratio of the sum of the mass of the first monomer, the second monomer and the third monomer to the mass of the prepolymerization solution is 5%-15%.

[0024] Furthermore, the ratio of the mass of the initiator to the sum of the mass of the first monomer, the second monomer and the third monomer is 0.4%-2%.

[0025] Furthermore, the initiator includes at least one of persulfate and azobisisobutylimidazoline hydrochloride.

[0026] Furthermore, the first monomer includes acrylic acid.

[0027] Furthermore, the second monomer includes at least one of acrylamide, N-vinyl caprolactam, N-tert-butyl acrylamide, N-octylacrylamide and N,N-methylenebisacrylamide.

[0028] Further, the third monomer includes at least one of α-olefin sulfonate, allyl sulfonate, methacrylic sulfonate, isethionic sulfonate, styrene sulfonate and p-styrene sulfonate.

[0029] Optionally, the prepolymerization solution is mixed with the negative electrode material, and after polymerization and drying, a negative electrode composite material is obtained. The polymerization temperature is 65° C.-80° C., and the polymerization time is 12 h-20 h.

[0030] Optionally, the prepolymer solution is mixed with the negative electrode material, and after polymerization and drying, a negative electrode composite material is obtained, the drying includes at least one of spray drying and vacuum drying, the inlet temperature of the spray drying is 110℃-180℃, the outlet temperature of the spray drying is 80℃-90℃, the temperature of the vacuum drying is 120℃-150℃, and the time of the vacuum drying is 20h-24h.

[0031] Optionally, the polymer solution is mixed with the negative electrode material and dried to obtain the negative electrode composite material, wherein the drying includes at least one of spray drying and vacuum drying, the inlet temperature of the spray drying is 110°C-180°C, the outlet temperature of the spray drying is 80°C-90°C, the temperature of the vacuum drying is 120°C-150°C, and the time of the vacuum drying is 20h-24h.

[0032] In a third aspect, the present application provides a negative electrode, comprising a negative electrode active material layer, wherein the negative electrode active material layer comprises the negative electrode composite material described in the first aspect, or the negative electrode composite material prepared by the preparation method described in the second aspect.

[0033] In a fourth aspect, the present application provides a battery, comprising a positive electrode and the negative electrode described in the third aspect.

[0034] In a fifth aspect, the present application provides an electrical device comprising the battery described in the fourth aspect.

[0035] The polymer layer in the negative electrode composite material provided by the present application has good flexibility and good bonding performance with the negative electrode material, which can avoid direct contact between the negative electrode material and the electrolyte, effectively slowing down and reducing the reaction between the negative electrode material and the electrolyte; the polymer layer can promote ion transport and improve ion conductivity; the polymer layer can participate in the formation of the SEI film and serve as the main skeleton of the SEI film. The SEI film formed by the polymer layer has high flexibility and can effectively avoid the occurrence of rupture, thereby reducing the consumption of lithium ions and improving the performance of the battery. The preparation method of the negative electrode composite material is simple and easy to operate, which is conducive to the use of the negative electrode composite material. The negative electrode and battery with the negative electrode composite material have excellent electrochemical properties, which is conducive to its use in electrical equipment and improves the product competitiveness of electrical equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the embodiments or the prior art description. The specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.

[0037] Figure 1 A schematic cross-sectional view of a negative electrode composite material provided in one embodiment of the present application.

[0038] Figure 2 A schematic cross-sectional view of a negative electrode provided in one embodiment of the present application. DETAILED DESCRIPTION

[0039] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0040] See also Figure 1 , is a cross-sectional schematic diagram of a negative electrode composite material provided in one embodiment of the present application, wherein the negative electrode composite material 100 includes a negative electrode material 10 and a polymer layer 20 wrapping the negative electrode material 10, and the material of the polymer layer 20 has a carboxyl group, an amide group and a sulfonic acid group. The polymer layer has good flexibility, and the carboxyl group and the amide group can form a bond with the negative electrode material, thereby improving the bonding performance between the polymer layer and the negative electrode material, so that the polymer layer can cover the negative electrode material for a long time, stably and relatively evenly, and can avoid direct contact between the negative electrode material and the electrolyte, and effectively slow down and reduce the reaction between the negative electrode material and the electrolyte; the polymer layer with carboxyl groups, amide groups and sulfonic acid groups can promote ion transport and improve ion conductivity; the polymer layer with carboxyl groups, amide groups and sulfonic acid groups can participate in the formation of the SEI film and serve as the main skeleton of the SEI film. The SEI film formed by the polymer layer has high flexibility and structural stability, which can effectively avoid the occurrence of rupture, thereby reducing the consumption of lithium ions, so that the negative electrode composite material has excellent coulomb efficiency, capacity, rate performance and cycle stability, which helps to improve the electrochemical performance of the battery. Compared with methods such as coating the surface of the negative electrode material with a carbon layer, an inorganic oxide layer, etc., the present application coats the negative electrode material with a polymer layer, which has better flexibility and coating properties, is not easy to break and fall off, and is more conducive to improving the performance of the negative electrode composite material and facilitating its use in batteries.

[0041] The negative electrode material in the present application can be selected from substances that can be used as negative electrode active materials for batteries. In one embodiment of the present application, the negative electrode material includes at least one of graphite and silicon-based materials. Among them, graphite has high specific energy, good chemical stability, and long cycle life, and silicon-based materials have high energy density and high specific capacity, which are all conducive to improving the performance of negative electrode composite materials. In one embodiment of the present application, graphite includes at least one of natural graphite and artificial graphite. Specifically, graphite can be purchased or obtained by recycling waste batteries. In some embodiments, graphite can be graphite with a carbon coating layer, that is, the surface of natural graphite or artificial graphite has a carbon coating layer, which further improves the conductivity of the negative electrode composite material. In one embodiment of the present application, the silicon-based material includes at least one of elemental silicon, silicon-oxygen material, silicon-carbon material and silicon alloy material. Among them, the silicon alloy material can include at least one of silicon-copper alloy, silicon-aluminum alloy, silicon-iron alloy and silicon-lithium alloy.

[0042] The negative electrode material of the present application can be a primary particle, a secondary particle, or a mixture of primary particles and secondary particles. In one embodiment of the present application, the particle size D50 of the negative electrode material is 8μm-16μm. Specifically, the particle size D50 of the negative electrode material can be but is not limited to 8μm, 8.5μm, 9μm, 10μm, 10.5μm, 11μm, 12μm, 13μm, 13.5μm, 14μm, 15.5μm, 15.5μm or 16μm, etc. The particle size D50 in the present application is the particle size corresponding to the cumulative particle size distribution volume percentage reaching 50%. The physical meaning is that the volume of particles with a particle size greater than the particle size D50 accounts for 50%, and the volume of particles less than the particle size D50 also accounts for 50%. D50 is also called the median diameter or median particle size.

[0043] In the present application, the polymer layer has a coating effect on the negative electrode material, and at the same time, when the negative electrode composite material is used in the battery, it participates in the formation of the SEI film, effectively improving the structural stability of the SEI film, which is beneficial to improving the electrochemical performance of the battery, and the carboxyl group, amide group and sulfonic acid group work synergistically to further improve the binding performance and coating performance of the polymer layer on the negative electrode material, as well as the stability of the formed SEI film. The material of the polymer layer in the present application is a three-dimensional network structure, so that the negative electrode material can be better stably and evenly coated, effectively avoiding contact between the negative electrode material and the electrolyte, improving the performance of the negative electrode material, and thus improving the performance of the battery. In one embodiment of the present application, the coverage rate of the polymer layer on the negative electrode material is greater than 90%. The coverage rate is the ratio of the positive projection area of ​​the polymer layer on the surface of the negative electrode material to the surface area of ​​the negative electrode material. Specifically, the coverage rate of the polymer layer on the negative electrode material is greater than 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99% or 100%, etc. In one embodiment of the present application, the coverage rate of the polymer layer on the negative electrode material is 100%, that is, the polymer layer completely covers the negative electrode material, thereby effectively avoiding direct contact between the electrolyte and the negative electrode material, and further improving the performance of the negative electrode material.

[0044] The material of the polymer layer in the present application is a copolymer. In one embodiment of the present application, the polymerized monomers of the copolymer include a first monomer, a second monomer and a third monomer, the first monomer includes a carboxyl group, the second monomer includes an amide group, and the third monomer includes a sulfonic acid group. That is to say, the first monomer, the second monomer and the third monomer copolymerize to form a polymer layer having a carboxyl group, an amide group and a sulfonic acid group. In one embodiment of the present application, the first monomer may include acrylic acid, thereby providing a carboxyl group. In one embodiment of the present application, the second monomer may also include at least one of an olefin group, a carboxyl group and a hydroxyl group, thereby facilitating the polymer between the first monomer, the second monomer and the third monomer. Exemplarily, the second monomer may include olefin amide. Specifically, the second monomer may include, but is not limited to, at least one of acrylamide, N-vinyl caprolactam, N-tert-butyl acrylamide, N-octyl acrylamide and N,N-methylenebisacrylamide. In one embodiment of the present application, the third monomer also includes at least one of an olefin group, a carboxyl group and a hydroxyl group, thereby facilitating the polymer between the first monomer, the second monomer and the third monomer. Exemplarily, the third monomer may include olefin sulfonate. Specifically, the third monomer may include, but is not limited to, at least one of α-olefin sulfonate, allyl sulfonate, methacrylate sulfonate, isethionate, styrene sulfonate and p-styrene sulfonate. Among them, the third monomer may be a sulfonic acid salt, such as at least one of a sulfonic acid sodium salt and a sulfonic acid potassium salt. In one embodiment of the present application, the copolymer includes an acrylic acid-olefin amide-olefin sulfonate copolymer. The carboxyl group in the copolymer can chemically bond with the oxygen-containing groups on the surface of the negative electrode material, and the amide group can also bond with the negative electrode material by hydrogen bonding, thereby improving the bonding performance and coating performance between the polymer layer and the negative electrode material; at the same time, the carboxyl group, amide group and sulfonic acid group can all participate in the formation of the SEI film, and are beneficial to the conduction of lithium ions, thereby improving the performance of the negative electrode composite material and the battery.

[0045] In this application, the polymer layer of the negative electrode composite material can be tested by Fourier transform infrared spectroscopy using a Thermo Fisher Nicolet iS50 FTIR spectrometer; for example, the 1650cm -1 ~1750cm -1 Peak position of C=O, 1320cm -1 ~1210cm -1 Peak position of CO, 3500cm -1 ~3100cm -1 Peak position of NH, 1420cm -1 ~1400cm -1 Peak position CN, 700cm -1 ~900cm -1The absorption peaks such as SO at the peak position collectively represent that the material of the polymer layer has carboxyl groups, amide groups and sulfonic acid groups. In this application, the Thermo Fisher K-Alpha X-ray Photoelectron Spectrometer (XPS) can also be used to detect the polymer layer of the negative electrode composite material; for example, the CN bond at 285eV to 286eV in the C1s signal spectrum, the C=O bond at 288eV to 289eV, the CN bond at ~400eV in the N1s signal spectrum, and the S=O at ~533eV in the O1s signal spectrum collectively represent that the material of the polymer layer has carboxyl groups, amide groups and sulfonic acid groups.

[0046] In one embodiment of the present application, the negative electrode material and the polymer layer are combined by hydrogen bonds. Among them, the carboxyl group and the amide group of the polymer layer can form hydrogen bonds with the oxygen-containing groups of the negative electrode material, thereby improving the bonding effect between the negative electrode material and the polymer layer. In one embodiment of the present application, an ester bond can also be formed between the negative electrode material and the polymer layer, thereby further improving the bonding effect between the negative electrode material and the polymer layer. Among them, the carboxyl group of the polymer layer can form an ester bond with the hydroxyl group on the surface of the negative electrode material by dehydration condensation.

[0047] In this application, the negative electrode composite material can be tested by Fourier transform infrared spectroscopy using a Thermo Fisher Nicolet iS50 FTIR spectrometer, but is not limited to the infrared spectrum at 3300 cm -1 ~3500cm -1 The strong and broad absorption peak at the peak represents the intermolecular hydrogen bond, ~1750cm -1 The peaks of C=O bond and 1210cm -1 ~1160cm -1 The CO bonds appearing at the peak position collectively represent ester bonds. Specifically, the completely discharged battery can be disassembled to obtain the negative electrode sheet, and the material can be scraped from any dressing area, placed in a centrifuge tube containing an ethanol solution, and then ultrasonicated in an ultrasonic cleaner for 20 minutes, filtered and dried to obtain the negative electrode composite material, and the hydrogen bonds and ester bonds therein can be detected.

[0048] In one embodiment of the present application, the thickness of the polymer layer is 1nm-80nm, which can not only coat the negative electrode material, but also will not affect the transmission of lithium ions, and can also serve as the main skeleton of the subsequent SEI film, improve the flexibility of the SEI film, and improve the performance of the negative electrode composite material and the battery. Specifically, the thickness of the polymer layer can be, but is not limited to, 1nm, 5nm, 8nm, 10nm, 13nm, 15nm, 17nm, 19nm, 20nm, 23nm, 25nm, 28nm, 30nm, 35nm, 40nm, 45nm, 48nm, 50nm, 53nm, 55nm, 57nm, 60nm, 65nm, 70nm, 75nm or 80nm, etc. In one embodiment of the present application, the thickness of the polymer layer can be 5nm-60nm, which has a better coating effect on the negative electrode material, and at the same time will not reduce the content of the negative electrode material in the negative electrode composite material, further improving the performance of the negative electrode composite material.

[0049] In one embodiment of the present application, the mass ratio of the polymer layer to the negative electrode material in the negative electrode composite material is 0.4%-8%, which not only ensures the coating effect of the polymer layer on the negative electrode material, but also ensures the flexibility of the SEI film formed subsequently, and also ensures the mass content of the negative electrode material in the negative electrode composite material, which is conducive to further improving the performance of the negative electrode composite material. Specifically, the mass ratio of the polymer layer to the negative electrode material in the negative electrode composite material can be, but is not limited to, 0.4%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.7%, 2%, 2.5%, 3%, 3.5%, 3.9%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5% or 8%, etc. In one embodiment of the present application, the mass ratio of the polymer layer to the negative electrode material in the negative electrode composite material can be 0.4%-5%, which further improves the performance of the negative electrode composite material.

[0050] In one embodiment of the present application, the particle size D50 of the negative electrode composite material is 8 μm-16.2 μm. Specifically, the particle size D50 of the negative electrode composite material can be, but is not limited to, 8 μm, 8.1 μm, 8.5 μm, 9 μm, 10 μm, 10.5 μm, 11 μm, 12 μm, 13 μm, 13.5 μm, 14 μm, 15.5 μm, 15.5 μm, 16 μm or 16.2 μm, etc. When measuring the particle size D50 of the negative electrode composite material, the test method specifically includes the following steps: a) disassembling the completely discharged battery to obtain the negative electrode sheet, and then cutting any position of the dressing area by argon ion to obtain a cross-sectional sample of the negative electrode sheet; b) placing the above-mentioned negative electrode sheet cross-sectional sample in SEM for observation, adjusting the electron microscope voltage, and the magnification to about 10k, to ensure that enough particles in the above-mentioned sample can be clearly seen and take pictures to obtain SEM photos; c) importing the obtained SEM photos into the grayscale debugging software (Geodict) to count the particle size of the particles; d) accumulating 20 experiments, and the number of particles counted in each experiment is not less than 500 pcs. After counting the above results, the median particle size D50 of the negative electrode composite material in the negative electrode sheet is obtained.

[0051] In one embodiment of the present application, the specific surface area of ​​the negative electrode composite material is 2 m 2 / g-4m 2 / g. The specific surface area of ​​the negative electrode composite material is small, which can effectively reduce the infiltration of the electrolyte and improve the performance of the negative electrode composite material. Specifically, the specific surface area of ​​the negative electrode composite material can be but is not limited to 2m 2 / g, 2.2m 2 / g, 2.4m 2 / g, 2.5m 2 / g, 2.7m 2 / g, 2m 2 / g, 3.3m 2 / g, 3.5m 2 / g, 3.8m 2 / g or 4m 2 In one embodiment of the present application, the specific surface area of ​​the negative electrode composite material can be 2.2 m 2 / g-3.8m 2 / g, further improving the performance of the negative electrode composite material.

[0052] In one embodiment of the present application, the first lithium removal capacity of the negative electrode composite material is greater than or equal to 350mAh / g. Specifically, the first lithium removal capacity of the negative electrode composite material is above 351mAh / g, above 352mAh / g, above 353mAh / g, above 354mAh / g, above 355mAh / g, above 357mAh / g or above 360mAh / g, etc. In one embodiment of the present application, the first coulombic efficiency of the negative electrode composite material is greater than or equal to 89%. Specifically, the first coulombic efficiency of the negative electrode composite material is above 90%, above 91%, above 92%, above 93%, etc. The negative electrode composite material was mixed with carbon black, sodium carboxymethyl cellulose, and styrene-butadiene rubber in a mass ratio of 96:1.5:1:1.5, then added to water and stirred evenly to form a slurry. The slurry was evenly coated on the copper foil using a coating machine. The electrode was placed in a vacuum drying oven at a temperature of 120°C for vacuum drying for 12 hours, and rolled to form an electrode. Then, a CR-2025 button lithium-ion battery was assembled in an argon-filled glove box. The lithium sheet was used as the counter electrode, the diaphragm was made of polypropylene, and the electrolyte solute was The electrolyte solvent is a mixed solution of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) (the volume ratio of the three is 1:1:1); the first cycle is 0.05C constant current discharge (lithium insertion) to 0.01V, and then constant voltage discharge with a cut-off current of 0.02C, followed by 0.05C constant current charging (lithium desorption) to 2.0V to test the first charge and discharge capacity and the first coulombic efficiency, and obtain the first lithium desorption capacity and the first coulombic efficiency.

[0053] The present application provides a method for preparing a negative electrode composite material, comprising: mixing a prepolymer solution with a negative electrode material, polymerizing and drying to obtain a negative electrode composite material, or mixing a polymer solution with a negative electrode material, and drying to obtain a negative electrode composite material. In other words, the prepolymer solution can be mixed with the negative electrode material, polymerized and dried to obtain a negative electrode composite material, or the polymer solution can be directly mixed with the negative electrode material, and dried to obtain a negative electrode composite material. The negative electrode composite material in any of the above embodiments can be prepared by this preparation method.

[0054] In one embodiment of the present application, the prepolymer solution includes a first monomer, a second monomer, a third monomer and an initiator, wherein the first monomer includes a carboxyl group, the second monomer includes an amide group, and the third monomer includes a sulfonic acid group. The specific selection of the first monomer, the second monomer and the third monomer is as described above and will not be repeated here; the first monomer, the second monomer and the third monomer can undergo a free radical polymerization reaction under the action of the initiator to form a copolymer.

[0055] In one embodiment of the present application, the mass ratio of the first monomer, the second monomer and the third monomer is (1-8): (1-3): (1-4), which is conducive to copolymerization between the first monomer, the second monomer and the third monomer to form a polymer layer. Specifically, the mass ratio of the first monomer, the second monomer and the third monomer can be, but is not limited to, (3-8): (2-3): (2-4), (4-8): (2-3): (3-4), (5-8): (1-3): (1-4) or (6-8): (1-3): (1-4), etc. In one embodiment, the mass ratio of the first monomer, the second monomer and the third monomer can be (5-8): (1-3): (1-4), and a high carboxyl content is conducive to the full progress of the polymerization reaction. At the same time, the content of the amide group and the sulfonic acid group also ensures that the subsequently formed polymer layer participates in the formation of the SEI film. Exemplarily, the mass ratio of the first monomer, the second monomer and the third monomer can be 1:1:1, 2:3:4, 5:3:1, 7:3:4 or 8:3:4, etc., wherein the first monomer can be acrylic acid, the second monomer can be alkenyl amide, and the third monomer can be sodium alkenyl sulfonate.

[0056] In one embodiment of the present application, the ratio of the mass of the first monomer, the second monomer and the third monomer to the mass of the prepolymer solution is 5%-15%, which not only ensures the mass content of the first monomer, the second monomer and the third monomer, is conducive to the formation of the polymer, but also ensures the polymerization reaction. Specifically, the ratio of the mass of the first monomer, the second monomer and the third monomer to the mass of the prepolymer solution can be, but is not limited to, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%, etc.

[0057] In one embodiment of the present application, the ratio of the mass of the initiator to the mass of the first monomer, the second monomer and the third monomer is 0.4%-2%, which ensures the polymerization reaction and is conducive to the formation of the copolymer. Specifically, the ratio of the mass of the initiator to the mass of the first monomer, the second monomer and the third monomer can be, but not limited to, 0.4%, 0.5%, 0.7%, 0.8%, 1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8%, 1.9% or 2%, etc. In one embodiment of the present application, the initiator includes at least one of persulfate and azobisisobutylimidazoline hydrochloride. Among them, the persulfate can include, but is not limited to, at least one of ammonium persulfate, potassium persulfate and sodium persulfate.

[0058] In the present application, the solvent of the prepolymer solution is used to dissolve and disperse the first monomer, the second monomer, the third monomer, the initiator and the negative electrode material, and the solvent of the prepolymer solution does not react with the above substances. Specifically, the solvent of the prepolymer solution includes at least one of methanol, ethanol, ether, isopropanol and dimethyl sulfoxide.

[0059] In the present application, the negative electrode materials such as graphite and silicon-based materials can be treated (such as low-temperature pre-oxidation) to make the surface of the negative electrode material have oxygen-containing groups such as hydroxyl groups, which is conducive to the combination between the negative electrode material and the polymer layer. In one embodiment of the present application, the mass ratio of the first monomer, the second monomer and the third monomer to the negative electrode material is 0.4%-8%, which not only ensures the coating effect of the polymer layer on the negative electrode material, but also ensures the flexibility of the SEI film formed subsequently, and also ensures the mass content of the negative electrode material in the negative electrode composite material, which is conducive to further improving the performance of the negative electrode composite material. Specifically, the mass ratio of the first monomer, the second monomer and the third monomer to the negative electrode material can be but not limited to 0.4%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.7%, 2%, 2.5%, 3%, 3.5%, 3.9%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5% or 8%, etc. In one embodiment of the present application, the mass ratio of the first monomer, the second monomer and the third monomer to the negative electrode material can be 1%-6%, further improving the performance of the negative electrode composite material. In one embodiment of the present application, the specific surface area of ​​the negative electrode material is 2.5m 2 / g-9m 2 / g. Specifically, the specific surface area of ​​the negative electrode composite material can be, but is not limited to, 2.5 m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g, 8m 2 / g or 9m 2 / g, etc.

[0060] In one embodiment of the present application, the polymerization temperature is 65°C-80°C, and the polymerization time is 12h-20h, which is conducive to full polymerization and contributes to the formation of a polymer layer. Specifically, the polymerization temperature may be, but is not limited to, 65°C, 67°C, 68°C, 70°C, 72°C, 75°C, 76°C, 78°C or 80°C, and the polymerization time may be, but is not limited to, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h or 20h, etc. In one embodiment of the present application, polymerization may be carried out under an inert atmosphere (such as argon, etc.) to improve the quality of the copolymer formed. In one embodiment of the present application, mixing and polymerization may be carried out at a stirring speed of 400r / min-800r / min to accelerate uniform mixing and accelerate polymerization.

[0061] In the present application, the solvent is removed by drying to form a negative electrode material coated with a polymer layer. At the same time, a dehydration reaction may occur during the drying process, so that an ester bond is generated between the polymer layer and the oxygen-containing groups of the negative electrode material, further enhancing the binding force between the two. In one embodiment of the present application, drying includes at least one of spray drying and vacuum drying. In one embodiment of the present application, the inlet temperature of spray drying is 110°C-180°C, and the outlet temperature of spray drying is 80°C-90°C. In one embodiment of the present application, the temperature of vacuum drying is 120°C-150°C, and the time of vacuum drying is 20h-24h.

[0062] In the method of polymerizing after mixing the prepolymer solution with the negative electrode material in the present application, multiple monomers are polymerized in situ in the blending with the negative electrode material, and the polymer mixed solution is directly mixed with the negative electrode material, which reduces the in situ polymerization process, wherein the polymer mixed solution is obtained by polymerization reaction of the prepolymer solution. The whole process is liquid phase and the preparation temperature is low, which can reduce the preparation cost and facilitate mass production. The thickness and structure of the polymer layer are highly controllable and flexible. The polymer layer formed by polymerization can be tightly combined with the surface of the negative electrode material, and the polymer distribution continuity is good, which can achieve uniform coating of the negative electrode material.

[0063] The present application provides a negative electrode, including a negative electrode active material layer, wherein the negative electrode active material layer includes the negative electrode composite material in any of the above embodiments, or the negative electrode composite material prepared in any of the above embodiments. The negative electrode having the negative electrode composite material has high first efficiency, excellent rate performance and cycle performance, which is conducive to its use in a battery.

[0064] In one embodiment of the present application, the mass content of the negative electrode composite material in the negative electrode active material layer is greater than or equal to 80%, which is beneficial to improving the electrochemical performance of the negative electrode. Specifically, the mass content of the negative electrode composite material in the negative electrode active material layer is greater than or equal to 82%, 85%, 88%, 90%, 93%, 95%, 97% or 98%, etc.

[0065] In one embodiment of the present application, the negative electrode active material layer may also include at least one of a negative electrode conductor and a negative electrode binder. Specifically, the negative electrode conductor may include but is not limited to at least one of conductive carbon black, carbon nanotubes, carbon fibers, carbon black and graphite; the negative electrode binder may include but is not limited to at least one of polytetrafluoroethylene, polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene latex, and nitrile rubber. In one embodiment of the present application, the mass content of the negative electrode conductor in the negative electrode active material layer is less than or equal to 5%. Specifically, the mass content of the negative electrode conductor in the negative electrode active material layer may be but is not limited to 0.1%, 0.5%, 1%, 2%, 3%, 4% or 5%, etc. In one embodiment, the mass content of the negative electrode conductor in the negative electrode active material layer may be 0.1%-5%. In one embodiment of the present application, the mass content of the negative electrode binder in the negative electrode active material layer is less than or equal to 10%. Specifically, the mass content of the negative electrode binder in the negative electrode active material layer may be, but is not limited to, 0.1%, 0.5%, 2%, 4%, 5%, 7%, 8% or 9%, etc. In one embodiment, the mass content of the negative electrode binder in the negative electrode active material layer is 0.1%-10%.

[0066] In one embodiment of the present application, the thickness of the negative electrode active material layer is 10 μm-100 μm, which can ensure the electrochemical performance of the negative electrode without increasing the weight of the negative electrode too much. Specifically, the thickness of the negative electrode active material layer can be, but is not limited to, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm or 100 μm, etc.

[0067] In one embodiment of the present application, the negative electrode further comprises a negative electrode current collector, and the negative electrode active material layer is disposed on the surface of the negative electrode current collector. Figure 2 , is a schematic cross-sectional view of a negative electrode provided in one embodiment of the present application, wherein the negative electrode 200 includes a negative electrode current collector 210 and a negative electrode active material layer 220 disposed on the surface of the negative electrode current collector 210, and the negative electrode active material layer 220 includes a negative electrode composite material. In one embodiment of the present application, the negative electrode current collector is selected from a metal foil or an alloy foil. Among them, the metal foil includes copper, aluminum, nickel, iron or cobalt foil, and the alloy foil includes an alloy of at least one element of copper, aluminum, nickel, iron and cobalt or stainless steel. In one embodiment, the material of the negative electrode current collector includes at least one of copper, aluminum, nickel, iron and cobalt or stainless steel. Specifically, the negative electrode current collector can be copper foil. In one embodiment of the present application, at least one of a binder and a conductive agent can be mixed with a negative electrode composite material in an organic solvent to form a mixed slurry, and the mixed slurry is coated on the surface of the negative electrode current collector, and the negative electrode is obtained after drying.

[0068] The present application provides a battery, comprising a positive electrode and a negative electrode in any of the above embodiments. The battery having the negative electrode has excellent first efficiency, rate performance and cycle performance, which is beneficial to the use of the battery. Specifically, the battery can be, but is not limited to, a lithium ion battery, etc.

[0069] In one embodiment of the present application, the positive electrode includes a positive electrode current collector and a positive electrode active material layer disposed on the surface of the positive electrode current collector. In one embodiment of the present application, the positive electrode current collector is selected from a metal foil or an alloy foil. Among them, the metal foil includes copper, titanium, aluminum, platinum, iridium, ruthenium, nickel, tungsten, tantalum, gold or silver foil, and the alloy foil includes stainless steel, or an alloy containing at least one element of copper, titanium, aluminum, platinum, iridium, ruthenium, nickel, tungsten, tantalum, gold and silver. Specifically, the positive electrode current collector can be aluminum foil.

[0070] In one embodiment of the present application, the positive electrode active material layer includes at least one of a positive electrode binder and a positive electrode conductor, and a positive electrode active material. Specifically, the positive electrode active material includes at least one of a layered structure oxide (such as lithium cobalt oxide, nickel cobalt manganese oxide ternary, nickel cobalt aluminum oxide ternary, transition metal layered oxide, etc.), a polyanion material (such as lithium iron phosphate, lithium iron manganese phosphate, sodium iron phosphate, sodium vanadium phosphate, etc.), and a spinel oxide (such as lithium manganese oxide, lithium nickel manganese oxide, etc.); the positive electrode conductor may include but is not limited to at least one of conductive carbon black, carbon nanotubes, carbon fiber, carbon black and graphite; the positive electrode binder may include but is not limited to at least one of polytetrafluoroethylene, polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene butadiene latex and nitrile rubber. In one embodiment, the mass content of the positive electrode active material in the positive electrode active material layer is greater than or equal to 80%, which is conducive to improving the electrochemical performance of the positive electrode. Specifically, the mass content of the positive electrode active material in the positive electrode active material layer is greater than or equal to 82%, 85%, 88%, 90%, 93%, 95%, 97% or 98%, etc. In one embodiment, the mass content of the positive electrode conductive agent in the positive electrode active material layer is less than or equal to 5%. Specifically, the mass content of the positive electrode conductive agent in the positive electrode active material layer may be, but not limited to, 0.1%, 0.5%, 1%, 2%, 3%, 4% or 5%, etc. In one embodiment, the mass content of the positive electrode conductive agent in the positive electrode active material layer may be 0.1%-5%. In one embodiment, the mass content of the positive electrode binder in the positive electrode active material layer is less than or equal to 10%. Specifically, the mass content of the positive electrode binder in the positive electrode active material layer may be, but not limited to, 0.1%, 0.5%, 2%, 4%, 5%, 7%, 8% or 9%, etc. In one embodiment, the mass content of the positive electrode binder in the positive electrode active material layer is 0.1%-10%.

[0071] In one embodiment of the present application, the battery also includes an electrolyte. In one embodiment of the present application, at least part of the positive electrode is immersed in the electrolyte, and at least part of the negative electrode is immersed in the electrolyte, so as to ensure the normal operation of the battery. In one embodiment of the present application, the electrolyte includes a solute and an organic solvent. Among them, the solute can be selected according to the type of battery, for example, the solute of the electrolyte in a lithium-ion battery can be a lithium salt. Specifically, the lithium salt may include but is not limited to at least one of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium perchlorate, lithium hexafluoroborate and lithium bistrifluoromethanesulfonyl imide; the organic solvent may include but is not limited to at least one of ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), vinylene carbonate (VC) and fluoroethylene carbonate (FEC).

[0072] The present application provides an electrical device, including a battery in any of the above embodiments. The battery in the electrical device provided in the present application has excellent electrochemical properties, thereby improving the performance and service life of the electrical device. Specifically, the electrical device may refer to a vehicle, an electronic device, an energy storage system, etc., and the above battery may be provided in the electrical device in the form of a single cell, a battery module, a battery pack, etc.

[0073] The effect of the technical solution of this application is further explained below through specific examples.

[0074] Example 1

[0075] Acrylic acid monomer, alkenyl amide monomer (acrylamide), sodium alkenyl sulfonate monomer (sodium allyl sulfonate) are added to a solvent (50% volume concentration of ethanol aqueous solution) in a mass ratio of 8:3:4, and then an initiator sodium persulfate is added (the ratio of the mass of the initiator to the mass of the above three monomers is 0.5%), and mixed evenly at room temperature; then spherical natural graphite (specific surface area 8.74m 2 / g), the mass of the above three monomers and the ratio of the mass of spherical natural graphite is 3%. Stirring (rotation speed is 700r / min) under argon atmosphere and in-situ polymerization reaction at 65°C for 12h to obtain a mixed solution. The mixed solution is spray dried (inlet temperature is 150°C, outlet temperature is 90°C), and cooled to obtain a negative electrode composite material, which includes graphite and a polymer layer wrapped around the graphite, and the material of the polymer layer is acrylic acid-vinyl amide-vinyl sulfonate copolymer.

[0076] Example 2

[0077] The method is substantially the same as Example 1, except that the ratio of the mass of the three monomers to the mass of the spherical natural graphite is 5%.

[0078] Example 3

[0079] The method is substantially the same as Example 1, except that the ratio of the mass of the three monomers to the mass of the spherical natural graphite is 0.4%.

[0080] Example 4

[0081] The method is substantially the same as Example 1, except that the ratio of the mass of the three monomers to the mass of the spherical natural graphite is 8%.

[0082] Example 5

[0083] The method is substantially the same as Example 1, except that the ratio of the mass of the initiator to the sum of the masses of the three monomers is 2%.

[0084] Example 6

[0085] The process is substantially the same as in Example 1, except that the polymerization temperature is 75°C.

[0086] Example 7

[0087] The process is substantially the same as Example 1, except that the polymerization time is 20 h.

[0088] Example 8

[0089] The method is substantially the same as Example 1, except that acrylic acid monomer, alkenyl amide monomer, and sodium alkenyl sulfonate monomer are added to the solvent in a mass ratio of 4:1:1.

[0090] Example 9

[0091] The method is substantially the same as Example 1, except that acrylic acid monomer, alkenyl amide monomer, and sodium alkenyl sulfonate monomer are added to the solvent in a mass ratio of 1:2:1.

[0092] Example 10

[0093] The process is substantially the same as in Example 1, except that the polymerization temperature is 80°C.

[0094] Embodiment 11

[0095] The process is substantially the same as in Example 1, except that the argon atmosphere is changed to an air atmosphere.

[0096] Example 12

[0097] It is substantially the same as Example 1, except that the spray drying is changed to vacuum drying (temperature is 150° C., time is 12 h).

[0098] Embodiment 13

[0099] The same as Example 1, except that the spherical natural graphite is replaced by carbon-coated natural graphite (specific surface area 3.5 m 2 / g).

[0100] Embodiment 14

[0101] The method is substantially the same as Example 1, except that the mass ratio of acrylic acid monomer, alkenyl amide monomer and sodium alkenyl sulfonate monomer is 8:1:1, and the ratio of the mass of the three monomers to the mass of spherical natural graphite is 8%.

[0102] Comparative Example 1

[0103] The spherical natural graphite in Example 1 was directly used.

[0104] Comparative Example 2

[0105] The method is substantially the same as Example 5, except that acrylic acid monomer and alkenyl amide monomer are added to the solvent at a mass ratio of 4:1, and sodium alkenyl sulfonate monomer is not included.

[0106] Comparative Example 3

[0107] The method is substantially the same as Example 5, except that acrylic acid monomer and sodium olefin sulfonate monomer are added to the solvent at a mass ratio of 4:1, and olefin amide monomer is not included.

[0108] Comparative Example 4

[0109] The method is substantially the same as Example 5, except that the alkenyl amide monomer and the sodium alkenyl sulfonate monomer are added to the solvent at a mass ratio of 3:4, and no acrylic acid monomer is contained.

[0110] Comparative Example 5

[0111] The method is substantially the same as Example 5, except that acrylic acid monomer is added to the solvent, and vinyl amide monomer and sodium vinyl sulfonate monomer are not included.

[0112] Comparative Example 6

[0113] The method is substantially the same as Example 5, except that the alkenyl amide monomer is added to the solvent, and the acrylic acid monomer and the sodium alkenyl sulfonate monomer are not included.

[0114] Comparative Example 7

[0115] The method is substantially the same as Example 5, except that sodium olefin sulfonate monomer is added to the solvent, and acrylic acid monomer and olefin amide monomer are not included.

[0116] Performance Testing

[0117] The BET specific surface area of ​​the products obtained in the above embodiment and comparative example was measured by a specific surface tester; the thickness of the polymer layer in the negative electrode composite material obtained in the above embodiment was measured by a transmission electron microscope. The results are shown in Table 1.

[0118] The products obtained in the above embodiments and comparative examples were mixed with carbon black, sodium carboxymethyl cellulose, and styrene-butadiene rubber in a mass ratio of 96:1.5:1:1.5, and then added to water and stirred to form a negative electrode slurry. The negative electrode slurry was evenly coated on the copper foil using a coating machine, and the electrode was placed in a vacuum drying oven at a temperature of 120°C for vacuum drying for 12 hours, and rolled to form a negative electrode sheet. Subsequently, a CR-2025 button lithium-ion battery was assembled in a glove box filled with argon gas, with a lithium sheet as the counter electrode, a diaphragm made of polypropylene, an electrolyte solute of 1M LiPF6, and an electrolyte solvent of a mixed solution of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) (the volume ratio of the three was 1:1:1).

[0119] The first cycle coulombic efficiency, rate performance and cycle performance of the battery prepared above were tested, and the results are shown in Table 1; wherein, the first cycle coulombic efficiency test: the first cycle was discharged at a constant current of 0.05C to 0.01V, then discharged at a constant voltage, the cut-off current was 0.02C, and then charged to 2.0V with a constant current of 0.05C; the rate performance test: discharged at a constant current of 0.05C to 0.01V, then discharged at a constant voltage, the cut-off current was 0.02C, and then charged to 2.0V with a constant current of 0.05C, After repeating the above steps three times, discharge at 0.2C to 0.01V, then discharge at constant voltage with a cut-off current of 0.05C, and then charge to 2.0V with 5C constant current; Cycle performance test: discharge at 0.05C constant current to 0.01V, then discharge at constant voltage with a cut-off current of 0.02C, and then charge to 2.0V with 0.05C constant current. After repeating the above steps three times, charge and discharge cycles are performed at a rate of 0.5C, and the charge and discharge range is 0.01V-2.0V.

[0120] Table 1 Performance test results

[0121]

[0122]

[0123] The specific surface area and polymer layer thickness of the negative electrode composite material prepared in the embodiment of the present application are suitable, and the material of the polymer layer is acrylic acid-alkenyl amide-alkenyl sulfonate copolymer, which has carboxyl, amide and sulfonic acid groups; Comparative Example 1 directly uses spherical natural graphite as the negative electrode material, which does not contain a polymer layer. Although the negative electrode composite materials provided in Comparative Examples 2 to 7 have a polymer layer covering spherical natural graphite, the polymer layer does not contain one or two of the carboxyl, amide and sulfonic acid groups. As can be seen from Table 1, the first cycle coulomb efficiency, first cycle lithium removal specific capacity, lithium removal specific capacity at 5C, and capacity retention rate after 200 cycles of the battery prepared by the negative electrode composite material provided in the embodiment of the present application are better than the performance of the battery prepared in Comparative Examples 1 to 7, especially better than Comparative Example 1. Therefore, the negative electrode composite material containing carboxyl, amide and sulfonic acid polymer layers provided in the present application can effectively improve the first cycle coulomb efficiency, rate performance and cycle performance of the battery, which is beneficial to the use of the battery.

[0124] The above is a preferred embodiment of the present application, but it should not be understood as limiting the scope of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application, and these improvements and modifications are also considered to be within the scope of protection of the present application.

Claims

1. A negative electrode composite material, characterized in that: The invention comprises a negative electrode material and a polymer layer wrapping the negative electrode material, wherein the material of the polymer layer has a carboxyl group, an amide group and a sulfonic acid group.

2. The negative electrode composite material according to claim 1, characterized in that: The polymerized monomers of the material of the polymer layer include a first monomer, a second monomer and a third monomer, the first monomer includes the carboxyl group, the second monomer includes the amide group, and the third monomer includes the sulfonic acid group.

3. The negative electrode composite material according to claim 2, characterized in that: The first monomer includes acrylic acid; The second monomer further comprises at least one of an olefinic group, a carboxyl group, and a hydroxyl group; The third monomer further includes at least one of an olefin group, a carboxyl group, and a hydroxyl group.

4. The negative electrode composite material according to any one of claims 1 to 3, characterized in that: The material of the polymer layer includes acrylic acid-alkenylamide-alkenylsulfonate copolymer.

5. The negative electrode composite material according to claim 1, characterized in that: There is a hydrogen bond between the negative electrode material and the polymer layer.

6. The negative electrode composite material according to claim 5, characterized in that: An ester bond is also formed between the negative electrode material and the polymer layer.

7. The negative electrode composite material according to claim 1, characterized in that: The thickness of the polymer layer is 1nm-80nm; The coverage rate of the polymer layer on the negative electrode material is greater than 90%; The particle size D50 of the negative electrode material is 8 μm-16 μm; The particle size D50 of the negative electrode composite material is 8 μm-16.2 μm; The specific surface area of ​​the negative electrode composite material is 2m 2 / g-4m 2 / g; The negative electrode material includes at least one of graphite and silicon-based materials; The mass ratio of the polymer layer to the negative electrode material in the negative electrode composite material is 0.4%-8%.

8. A method for preparing a negative electrode composite material, characterized in that: include: The prepolymer solution is mixed with the negative electrode material, and after polymerization and drying, a negative electrode composite material is obtained, or the polymer solution is mixed with the negative electrode material, and after drying, the negative electrode composite material is obtained. The negative electrode composite material includes the negative electrode material and a polymer layer wrapping the negative electrode material, and the material of the polymer layer has carboxyl group, amide group and sulfonic acid group.

9. The preparation method according to claim 8, characterized in that: The prepolymer solution comprises a first monomer, a second monomer, a third monomer and an initiator, wherein the first monomer comprises the carboxyl group, the second monomer comprises the amide group, and the third monomer comprises the sulfonic acid group; The mass ratio of the first monomer, the second monomer and the third monomer is (1-8):(1-3):(1-4); The ratio of the sum of the mass of the first monomer, the second monomer and the third monomer to the mass of the prepolymerization solution is 5%-15%; The ratio of the mass of the initiator to the mass of the first monomer, the second monomer and the third monomer is 0.4%-2%; The initiator comprises at least one of persulfate and azobisisobutylimidazoline hydrochloride; The first monomer includes acrylic acid; The second monomer includes at least one of acrylamide, N-vinyl caprolactam, N-tert-butyl acrylamide, N-octylacrylamide and N,N-methylenebisacrylamide; The third monomer includes at least one of α-olefin sulfonate, allyl sulfonate, methacrylic sulfonate, isethionic sulfonate, styrene sulfonate and p-styrene sulfonate.

10. The preparation method according to claim 8, characterized in that: The prepolymerization solution is mixed with the negative electrode material, and after polymerization and drying, a negative electrode composite material is obtained. The polymerization temperature is 65° C.-80° C., and the polymerization time is 12 h-20 h.

11. The preparation method according to claim 8, characterized in that: The prepolymer solution is mixed with the negative electrode material, polymerized and dried to obtain a negative electrode composite material, wherein the drying includes at least one of spray drying and vacuum drying, the inlet temperature of the spray drying is 110°C-180°C, the outlet temperature of the spray drying is 80°C-90°C, the temperature of the vacuum drying is 120°C-150°C, and the time of the vacuum drying is 20h-24h; or The polymer solution is mixed with the negative electrode material and dried to obtain the negative electrode composite material, wherein the drying includes at least one of spray drying and vacuum drying, the inlet temperature of the spray drying is 110°C-180°C, the outlet temperature of the spray drying is 80°C-90°C, the temperature of the vacuum drying is 120°C-150°C, and the time of the vacuum drying is 20h-24h.

12. A negative electrode, characterized in that: The invention comprises a negative electrode active material layer, wherein the negative electrode active material layer comprises the negative electrode composite material according to any one of claims 1 to 7, or the negative electrode composite material prepared by the preparation method according to any one of claims 8 to 11.

13. A battery, characterized in that: It comprises a positive electrode and the negative electrode as claimed in claim 12.

14. An electrical device, characterized in that: Comprising the battery of claim 13.

Citation Information

Cited By

  • Battery negative electrode, secondary battery, negative electrode material and preparation method of negative electrode material

    CN120545327A

  • Negative electrode composite material, preparation method therefor, negative electrode, battery, and electrical device

    WO2025214281A1